2016
DOI: 10.5665/sleep.6230
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Insomnia Disorder: An Exploratory Cluster Analysis of Objective Sleep Parameters Reveals Differences in Neurocognitive Functioning, Quantitative EEG, and Heart Rate Variability

Abstract: Insomnia 100 sleep study: Australia New Zealand Clinical Trials Registry (ANZCTR) identification number 12612000049875. URL: https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=347742.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 55 publications
2
61
0
Order By: Relevance
“…Insomnia with NNSD is related with an anxious‐ruminative profile (Vgontzas et al., ), whereas insomnia with OSSD is linked with physiological hyperarousal (Vgontzas et al., ), increased risk of type 2 diabetes, hypertension, as well as concurrent and future cerebrovascular and cardiovascular events (Fernandez‐Mendoza et al., ; Vgontzas et al., ). Despite data on the link between insomnia and OSSD with cardiometabolic disease (Fernandez‐Mendoza et al., ; Kalmbach, Pillai, Arnedt, & Drake, ; Vgontzas et al., ), information on potential underlying pathophysiological mechanisms, such as systematic inflammation (Fernandez‐Mendoza et al., ), hormonal and metabolic dysregulation (D'Aurea et al., ; Fernandez‐Mendoza et al., ), or alterations in the autonomic nervous system (Miller et al., ; Spiegelhalder et al., ) have been scant.…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia with NNSD is related with an anxious‐ruminative profile (Vgontzas et al., ), whereas insomnia with OSSD is linked with physiological hyperarousal (Vgontzas et al., ), increased risk of type 2 diabetes, hypertension, as well as concurrent and future cerebrovascular and cardiovascular events (Fernandez‐Mendoza et al., ; Vgontzas et al., ). Despite data on the link between insomnia and OSSD with cardiometabolic disease (Fernandez‐Mendoza et al., ; Kalmbach, Pillai, Arnedt, & Drake, ; Vgontzas et al., ), information on potential underlying pathophysiological mechanisms, such as systematic inflammation (Fernandez‐Mendoza et al., ), hormonal and metabolic dysregulation (D'Aurea et al., ; Fernandez‐Mendoza et al., ), or alterations in the autonomic nervous system (Miller et al., ; Spiegelhalder et al., ) have been scant.…”
Section: Introductionmentioning
confidence: 99%
“…There have been previous attempts to identify nighttime and daytime symptom cluster profiles in patients with insomnia disorder using data-driven approaches. [8][9][10][11][12][13] Similar attempts have been published characterizing the heterogeneity of obstructive sleep apnea. 14,15 However, most of these studies used cluster analysis to characterize this heterogeneity.…”
Section: Introductionmentioning
confidence: 66%
“…A number of studies have highlighted differential outcomes associated with short versus long objective sleep. [38][39][40][41][42]59 In contrast to these top-down approaches, data-driven methods, such as cluster analysis, have been applied to this area and have revealed that daytime symptoms such as sleepiness, fatigue, mood and sleep hygiene practices, 9 nighttime symptoms such as objective sleep parameters, 10 night-to-night variability and longitudinal development of subjective sleep variables, 11,17 and dysfunctional beliefs about sleep 12 uniquely fall together in identifiable and meaningful clusters. Others have used both sleep and psychiatric history, and daytime and nighttime symptoms to identify symptom clusters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations